Perilaku Pekerasan Verbal Melalui Media Sosial Pada Remaja - Nur A, Sherly; Hambali, IM.; Indreswari, Henny (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
The purpose of this study was to provide information on the description of verbal violent behavior, the causes of verbal violence, and the impact of verbal violent behavior. The research method that the researchers used was qualitative, This research was studied in the design of a case study on adolescents at SMA Nurul Muttaqin Malang consisting of 3 informants, The data collection used by the researcher was secondary data and primary data, and three data collection techniques in the form of observation, interviews and documentation. The results of this study are 1) Researchers found similarities with the exposure of the teenagers interviewed because they almost had the same problems in their lives, such as friendships that were friends who had almost the same personality, personal and family with the same problems, 2) The form of verbal violence behavior carried out by adolescents in accordance with previous theories was only that this was done on social media in the form of harsh sentences and words thrown through social media, and 3) this research has many limitations so that further research is needed to be more accommodating so that it has a deeper and comprehensive understanding.